2017
DOI: 10.1051/0004-6361/201731064
|View full text |Cite
|
Sign up to set email alerts
|

Measuring solar active region inflows with local correlation tracking of granulation

Abstract: Context. Local helioseismology has detected spatially extended converging surface flows into solar active regions. These play an important role in flux-transport models of the solar dynamo. Aims. We aim to validate the existence of the inflows by deriving horizontal flow velocities around active regions with local correlation tracking of granulation. Methods. We generate a six-year long-time series of full-disk maps of the horizontal velocity at the solar surface by tracking granules in continuum intensity ima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(85 citation statements)
references
References 31 publications
8
74
3
Order By: Relevance
“…However, the predominance of 10 m s −1 retrograde flows towards the polar side of ARs is plausibly consistent with the net cyclonic circulation of ∼ 5 m s −1 found by Hindman et al (2009) around AR peripheries. On the other hand, the retrograde flows do not readily appear in the ensemble averaged flow map shown in Figure 8 of Löptien et al (2017). This discrepancy is not understood, but may result from differences in the background trend removal or other details in the analyses.…”
Section: Discussionmentioning
confidence: 97%
“…However, the predominance of 10 m s −1 retrograde flows towards the polar side of ARs is plausibly consistent with the net cyclonic circulation of ∼ 5 m s −1 found by Hindman et al (2009) around AR peripheries. On the other hand, the retrograde flows do not readily appear in the ensemble averaged flow map shown in Figure 8 of Löptien et al (2017). This discrepancy is not understood, but may result from differences in the background trend removal or other details in the analyses.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the activity-related meridional flow pattern may partly originate from the superposition of more localized circular inflows towards individual active regions (Haber et al 2004;Š vanda et al 2008;Löptien et al 2017). It is unclear whether such concentric flows can exert a torque on the flux loops that may reduce their tilt; however this may not even be necessary: simulations by Martin-Belda and suggested that the hindering effect on the inflows on the separation of leading and trailing polarity fluxes is sufficient to significantly reduce the amplitude of the dipolar seed field being built up for the next cycle.…”
Section: Alternatives To Tilt Quenching: Inflows and Latitude Quenchingmentioning
confidence: 99%
“…We used an updated version of the flow maps generated by Löptien et al (2017), who described their processing procedure in detail. We summarize the important aspects below.…”
Section: Flows Inferred From Local Correlation Trackingmentioning
confidence: 99%
“…This work showed that the amplitude of the flows increases with magnetic flux, and reported a retrograde flow component mainly at the poleward side and, less distinct, the equatorward side of the AR. Löptien et al (2017) used local correlation tracking (LCT, November & Simon 1988) of the convective granulation pattern on the solar surface to measure inflows around an average highflux AR. The regions in their sample have fluxes higher than 5.9×10 21 Mx.…”
Section: Introductionmentioning
confidence: 99%